(untitled) (Revista de Física Médica, 2025)
Nowadays, surfaces guidance systems allow patient positioning with accuracies of less than one milimeter. Good patient immobilization is essential to achieve this accuracy. For treatment of extremities, have been used different generalized solutions, such as thermoplastic masks or vacuum mattress. This study aims to achieve personalized immobilization, which combines precision and comfort for the patient during treatment. To achieve this, a design oriented to additive manufacturing technology is being developed. The first step is to characterize which type of biocompatible material has the best dosimetric characteristics to be able to manufacture the immobilizer by 3D printing. In addition to the dosimetric characteristics, it is important that these materials have ergonomic criteria that allow better reproducibility and precision in radiotherapy treatments located in the extremities. Different materials have been analyzed taking into account these properties, selecting the most appropriates ones in order to design and implement the proof of concept of an extremities immobilizer in daily clinical routine. The study carried out in this research project reflects that the most suitable materials for the customized design of the extremities immobilizer by 3D printing are PLA for the support part of the immobilizer and Easyl925 as the bolus material.